SYSTEM AND METHOD FOR BREATHING PATTERN EXTRACTION FROM PPG SIGNALS - Ghose, Avik; Jani, Dhaval Satish; Jaiswal, Dibyanshu; Mukhopadhyay, Shalini (2019)
A system and method for extracting breathing patterns from PPG signals are provided. The method includes designing a filter for extracting breathing patterns from PPG signals. Designing the filter includes defining filter specifications for extraction of breathing pattern from the PPG signals. Herein, the filter specifications includes a type, an order and a cut-off frequency of the filter. Designing the filter further includes generating a transfer function associated with the filter specifications, and computing a plurality of filter coefficients using filtfilt function for allowing filtering of the PPG signals. Using the filter comprising the plurality of filter coefficients, a filtered PPG signal is generated by removing DC component from PPG signals obtained from a wearable device being worn by a subject. The filtered PPG signal is indicative of the breathing pattern of the subject.